2015
DOI: 10.1890/15-0968.1
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of Alaska paper birch (Betula neoalaskana): latitudinal patterns in chemical defense and plant architecture

Abstract: 25The latitudinal herbivory-defense hypothesis (LHDH) predicts that plants near the equator will 26 be more heavily defended against herbivores than are plants at higher latitudes. Although this 27 idea is widely found in the literature, recent studies have called this biogeographic pattern into 28 question. We sought to evaluate the LHDH in a high-latitude terrestrial ecosystem where fire and 29 mammalian herbivores may contribute to selection for higher levels of defensive chemistry. To 30 address this objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…For example, resource limitation may enforce stronger trade-offs for highly defended species from stressful habitats compared with species originating from less stressful habitats (Hahn and Maron 2016;Robinson and Strauss 2018). Chemically defended species like milkweeds (Woods et al 2012) and mints (Rokaya et al 2016) or slow-growing species like boreal trees (Stevens et al 2016) and sagebrush (Pratt and Mooney 2013) may be more likely to exhibit growth-defense trade-offs across populations than less defended fast-growing species. In our study, although we found that most pairwise correlations were neutral or positive, we did find some evidence for trade-offs between growth and a chemical defense (i.e., cardenolides) in the common garden.…”
Section: Generalizing Across Species and Gradientsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, resource limitation may enforce stronger trade-offs for highly defended species from stressful habitats compared with species originating from less stressful habitats (Hahn and Maron 2016;Robinson and Strauss 2018). Chemically defended species like milkweeds (Woods et al 2012) and mints (Rokaya et al 2016) or slow-growing species like boreal trees (Stevens et al 2016) and sagebrush (Pratt and Mooney 2013) may be more likely to exhibit growth-defense trade-offs across populations than less defended fast-growing species. In our study, although we found that most pairwise correlations were neutral or positive, we did find some evidence for trade-offs between growth and a chemical defense (i.e., cardenolides) in the common garden.…”
Section: Generalizing Across Species and Gradientsmentioning
confidence: 99%
“…Similarly, among milkweed species, tropical species tend to be more chemically defended, whereas temperate species tend to be less defended but more clonal (Pellissier et al 2016). Information on the habitat in which a species evolved, therefore, seems critical for describing intraspecific growthdefense strategies (Rokaya et al 2016;Stevens et al 2016;Robinson and Strauss 2018) and, importantly, correlations among growth and defense may differ depending on the traits being compared.…”
Section: Generalizing Across Species and Gradientsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, plant species growing in nutrientpoor soils invest more in chemical defences relative to species growing in nutrient-rich soils (Coley et al 1985, Coley andBarone 1996), and such effects may operate concurrently with herbivory along latitudinal gradients (Johnson andRasmann 2011, Abdala-Roberts et al 2016a). Further, the effect of abiotic factors may not vary latitudinally or may show latitudinal trends opposite to those of herbivory which may lead to unexpected latitudinal trends in plant defence investment (Abdala-Roberts et al 2016a, Stevens et al 2016. Therefore, addressing the simultaneous effects of multiple abiotic drivers is necessary for understanding how abiotic forcing influences plant traits, herbivores, or both along latitudinal gradients.…”
Section: Introductionmentioning
confidence: 99%